PERLINDUNGAN HUKUM TERHADAP WARGA SIPIL DALAM KONFLIK BERSENJATA (NON-INTERNASIONAL) LIBYA DITINJAU DARI PERSPEKTIF HUKUM HUMANITER INTERNASIONAL - Swarsih Wulandari, Pande Putu; Supasti Darmawan, Ni Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Lately a lot of armed conflict between the government and armed groups, categorized as a non-international armed conflict, one of them is armed conflict in Libya. A civil war or a war Libya is an armed conflict that occurred in 2011, the Libyan government led by Muammar al-Qaddafi against the rebels NTC (National Transitional Council). According to the First Report of the Prosecutor of the International Criminal Court to the UN Security Council Pursuant to UNSCR 1970 (2011), paragraphs 19 and 20 state the number of total deaths since the start of the conflict in the thousands, even reaching the 10,000 mark, as stated by the Libyan National Interim Council (INC). More than 50,000 people were injured. It is certainly get a protest from the international community considers that the actions of the government of Muammar Gaddafi is totally not with compassion and threaten world peace, so that victims, especially civilians must receive adequate protection.
Keywords: Protection, Civilian, Non-International Armed Conflicts